Echogenicity as a standalone nodule characteristic is not inferior to the TIRADS systems in the 10–20 mm nodule diameter range in patient selection for fine needle aspiration: a pilot study - Rucz, Karoly; Hegedűs, Laszlo; Bonnema, Steen Joop; Frasoldati, Andrea; Jambor, Laszlo; Kovacs, Gabor Laszlo; Papini, Enrico; Russ, Gilles; Karanyi, Zsolt; Nagy, Endre V; Solymosi, Tamas (European thyroid journal, 2024)
The ultrasound evaluation of thyroid nodules (TNs) in patient selection for fine needle aspiration (FNA) requires both uniformly accepted definitions of each nodule characteristic and extensive experience from the examiner. We hypothesized that nodule echogenicity alone may provide comparable performance to more complex approaches in patient selection for FNA. Seven highly experienced investigators from four countries evaluated, online, the ultrasound (US) video recordings of 123 histologically verified TN by answering 17 nodule characteristics-related questions. The diagnostic performances of five TN image reporting and data systems (TIRADS) were compared to making decisions based solely on the echogenicity of the nodule for indicating FNA in 110 nodules ≥10 mm. In the 10-20 mm size range, the sensitivities and specificities of the five TIRADS systems in identifying malignant nodules were 80.5-91.0% and 31.4-50.9%, respectively. Had FNA been recommended for all hypoechoic nodules, disregarding other US characteristics, comparable sensitivity and specificity (87.5% and 43.4%, respectively) were obtained. Compared to nodules >20 mm, a higher proportion of cancers were hypoechoic in the 10-20 mm size range (87.2% vs 77.8%, P = 0.05). In the 10-20 mm size range, compared to hypoechoic nodules, a significantly lower proportion of isoechoic nodules demonstrated suspicious findings (70.7% vs 30.0%, P < 0.05). In contrast to >20 mm diameter nodules, the recommendation of FNA may rely on a single US feature, echogenicity, in the 10-20 mm size range. If independently confirmed in larger cohorts, this may simplify nodule evaluation in this size range.